Towards carbon neutrality by implementing carbon emissions trading scheme: Policy evaluation in China - Chen, Xing; Lin, Boqiang (Energy policy, 2021)
The Carbon Emission Trading Scheme is generally considered an important market-oriented environmental policy tool aiming at carbon abatement. Therefore, the government and policymakers should focus on the positive role it plays. In September 2020, China proposed to achieve carbon neutrality by 2060. Based on the background of carbon neutrality, this paper, therefore, examines the policy effectiveness of carbon trading in two stages by taking the natural experiment of China's pilot as a case. The first stage constructs two indicators to represent the performance of energy utilization and carbon emissions by employing the global DEA, namely the total-factor carbon performance index and the energy-carbon performance index. The second stage discusses the policy effect of carbon trading by using the synthetic control method to construct unobservable counterfactual paths. The paper found that carbon trading can significantly improve carbon/energy-carbon performance. This empirical work identifies the role of the carbon trading scheme in promoting energy conservation and emission reduction, which is regarded as an effective policy tool to promote carbon neutrality. The placebo test also confirmed that the results are robust and significant. Finally, some policy suggestions are provided for achieving carbon neutrality worldwide based on these findings. •DEA model and synthetic control method are employed in this paper.•This paper takes the natural experiment of China's pilot CETS as a case study.•Whether CETS is an effective policy tool to promote carbon neutrality is verified.•CETS can improve carbon/energy-carbon performance to reduce emissions.•Suggestions on carbon neutrality and national CETS construction are put forward.